Weighted activity unit effect: evaluating the cost of diagnosis‐related group coding. Issue 4 (8th April 2020) - Tan, Joanne Y.‐A.; Senko, Clare; Hughes, Brett; Lwin, Zarnie; Bennett, Richard; Power, John; Thomson, Leah
Abstract: Background: Activity‐based funding (ABF) is a means of healthcare reimbursement, where hospitals are allocated funding based on the number and mix of clinical activity. The ABF model is based solely on Australian refined diagnosis‐related group (AR‐DRG) classifications of hospital encounters. Each AR‐DRG is allocated a weighted activity unit (WAU) translating to cost value to determine ongoing funding allocations for each hospital annually. Aim: We explored cost consequences of AR‐DRG coding variances within our Medical Oncology department over a 6‐month period. Methods: All inpatient encounters for medical oncology from 1 January to 30 June 2014 were identified and paired with actual AR‐DRG coding sheets submitted by the hospital coders. Inpatient charts were manually reviewed by a Medical Oncology Registrar to capture any changes or additional AR‐DRGs, which were subsequently evaluated for total WAU value variance. Applying 1 WAU = 4676 as per the 2014 Queensland model, cost consequences were calculated. Results: A total of 116 encounters was identified for 72 patients. Of 116 patients, 95 (81%) had additional diagnoses captured, leading to an AR‐DRG and WAU change in 26 encounters. The total reimbursement variance for this period was 143 404.07. Cost consequences resulted from: (i) use of abbreviations in clinical notes unable to be coded; and (ii) diagnoses not documented despite treatment delivered as per medication charts. Conclusion: Clinical note documentation ultimately determines the future funding of our healthcare system. Appropriate communication and education of medical staff and hospital coders are vital to ensure precise documentation and accurate AR‐DRG coding for optimal and appropriate reimbursement in this funding model.